Older Adults’ Knowledge and Perceptions of Whole Foods as an Exercise Recovery Strategy - Hayes, Eleanor Jayne; Granic, Antoneta; Hurst, Christopher; Dismore, Lorelle; Sayer, Avan A.; Stevenson, Emma (Frontiers in Nutrition, 2021)
Resistance exercise is a widely advocated treatment for improving muscle strength and performance in older adults. Maximising the benefit of resistance exercise by ensuring optimal recovery is an important aim and studies are now seeking interventions to expedite exercise recovery in older people. A recovery strategy that has acquired considerable interest is the consumption of protein, and more recently, the consumption of protein-rich whole foods. This study aimed to understand the perspectives of community-dwelling older adults, and determine their knowledge of exercise recovery strategies, their preferences for recovery strategies, and their attitudes towards using whole foods, such as milk as a post-exercise recovery aid. 291 older adults (74 ± 4 years) were recruited to complete a self-administered online survey. A mixed methods approach was used to gather in-depth data from the cohort. Participants were asked to complete a combination of free-text (open-ended) and multiple-choice questions. Content analysis was conducted on responses to open-ended questions through a systematic classification process of coding. The most common recovery strategies reported were heat treatment, rest, and massage. Nutrition was rarely cited as a recovery strategy. Less than 2% of respondents mentioned nutrition, of these, only half mentioned a protein source. 49% expressed negative opinions towards recovery supplements (e.g. “waste of money”) compared to 7% expressing positive opinions. Whole foods such as milk, meat, fish, and fruit, were deemed to be a more acceptable recovery strategy than supplements by 80% of respondents. Those that found whole foods to be equally as acceptable (18%), cited efficacy as their main concern, and those that declared whole foods less acceptable (2%) had no common reason. Despite the high acceptability of whole foods, only 35% were aware that these foods could aid recovery. When asked about milk specifically, the majority of older adults (73%) said this would, or might, be an acceptable exercise recovery strategy. Those that found milk an unacceptable recovery strategy (27%) often cited disliking milk or an allergy/intolerance. In conclusion, whilst whole foods represented an acceptable recovery intervention for older adults, the majority were unaware of the potential benefits of nutrition for post-exercise recovery.